ANALISIS PENGARUH PENGALAMAN MEREK TERHADAP NIAT PEMBELIAN ULANG DENGAN NILAI YANG DIRASAKAN DAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Studi pada Kopi Janji Jiwa di Kota Semarang) - Yasifa, Naila Ayu; Idris, Idris (Diponegoro Journal of Management, 2024)
ABSTRACT Semarang city as the capital of Central Java province with its various easy access can be an option for developing business. This is an opportunity for business development in the F&B (Food and Beverages) sector, such as the coffee shop business. In an effort to win competition from many coffee shop outlets in the long term, innovative strategies are needed as a differentiator from competitors that can keep this business in demand by customers. This research aims to prove the influence of the relationship between brand experience on repurchase intentions through customer perceived value and customer satisfaction (study on Kopi Janji Jiwa in Semarang City). The data collected came from the results of distributing questionnaires to 130 respondents with the criteria being at least 17 years old, domiciled in Semarang, and having purchased Jani Jiwa coffee in the city of Semarang at least once. The results of the data collection were then analyzed quantitatively and structurally using the SEM-PLS (Partial Least Square) method using SmartPLS version 4. The results of this study prove that brand experience has a positive and significant effect on repurchase intention, brand experience has a positive and significant effect on customer perceived value, customer perceived value has a positive and significant effect on customer satisfaction, customer perceived value has a positive and significant effect on Repurchase intention and customer satisfaction have a significant positive effect on repurchase intention. The managerial implication that can be applied is to use this research as a consideration for Kopi Janji Jiwa in serving its customers when consuming Janji Jiwa coffee, so that customers get a positive experience and value.